Potential usefulness of viral capsid surface proteins (VP1,VP2, VP3 & VP4) for vaccination against common cold - Alshrari, Ahmed Subeh D (2016)
Rhinoviruses (RVs) represent the most important etiological agents of the common cold and it is responsible for about two-thirds of acute exacerbations of chronic bronchitis, asthma and chronic obstructive pulmonary disease (COPD) in both children and adults. At present, there is no effective and approved antiviral therapies for either the prevention or treatment of diseases caused by RV infections. Furthermore, there are more than 100 types of RVs with high sequence variability hindering the progression of vaccine development. Bioinformatics tools, combined with the availability of complete genome sequence of all known RV types, provides a unique opportunity to enhance the optimal selection of potential immune targets. In vitro production or synthetic versions of these targets could be a possible alternative approach to the vaccine of choice. This study was carried out with the aim to develop a pan-serotypic vaccine that is capable of inducing the production of crossreactive antibodies that cover all or most of the RV serotypes. Firstly, a bioinformatics analysis was carried out to characterise the capsid proteins (VP1, VP2, VP3 and VP4) of all known RV serotypes and to predict potential immune motifs. In brief, complete protein sequences of each of the 100 distinct RV genomes were downloaded from the GenBank database. The sequences obtained were grouped based on their original classification [RV-A divided into two subgroups, minor LDLR(n=10) and major ICAM(n=65), and RV-B group (n=25)]. Upon grouping, sequence editing was carried out using a number of software in order to study each protein individually. The edited protein sequences were then aligned and analysed for sequence conservation, variability and to generate consensus sequences and distance matrices. This led to determining the relations between strains and identifying the ideal ones that are highly identical to others. Conserved motifs consisting at least nine-mers common across all RV-A or B serotypes (minor/major receptor) and exhibiting at least 80% representation were selected and synthesized chemically. These peptides were used alone or in combination to vaccinate groups of rabbits. On the other hand, four tagged fulllength genes coding the capsid proteins of an ideal strain (HRV-74), VP1, VP2, VP3 and VP4, whose codon uses were optimized, were constructed and cloned in vitro. Upon expression, the purified recombinant proteins adsorbed into incomplete Freund's adjuvant (IFA) as a single or combined proteins were also administered subcutaneously to other groups of rabbits. The responses and cross-reactivity of the specific immunoglobulin M (IgM) and G (IgG) to the peptides, proteins and whole viruses were measured by in-house indirect enzyme-linked immunosorbent assay (ELISA). Moreover, in vitro cross-neutralizing antibody titres against several variant strains of RV were also measured. Based on the bioinformatics analysis, 7, 8, 5 and 3 conserved regions were found among minor receptor serotypes for VP1, VP2, VP3 and VP4, respectively. The analysis of RV-A ICAM-receptor serotypes showed 3 conserved regions in each of VP1, VP2 and VP4, while 4 conserved regions were found upon alignment of VP3 sequences, respectively. The study also showed that the capsid protein of HRV-B contained at least one conserved site upon multiple sequences alignments of each protein separately. Furthermore, the analysis revealed that 72% of VP4 sequence (69 amino acids in length) as highly conserved among the RV-A major receptor group, but VP3 did not show well conserved regions. The current study also showed that VP4 sequences of the minor receptor groups (n=10) contained three highly conserved sites which accounted for 85% of its total length. RV-B VP4, in contrast,contained less conserved regions which exhibited only 25% of the protein's total length. Upon multiple sequence alignment of all RV-A, three highly conserved region were identified for each of the VP1, VP2 and VP4, while VP3 did not contain any. Based on distance matrices analysis, HRV-74 was found to be the ideal strain for vaccine development. VP1 amino acid sequence of HRV-74 was found to be identical by 80% or more of 22 serotypes, with a median identity of 75% within the RV-A group. Also, the analysis revealed HRV-74 as having the highest homology (86%) to the VP1 consensus sequence of all RV-A. A further analysis showed that HRV-74 is fully identical (100%) to the consensus sequence of RV-A VP4. Therefore, HRV-74 has been considered as the source genetic information of the recombinant proteins produced in this study. Antibodies raised to the synthetic peptides exhibited cross-reactivity against the corresponding recombinant proteins and antigenically distinct RV strains coated on plates via ELISA assay. Moreover, the specific immunoglobulin G (IgG) response to the peptides given in combination exhibited greater reactivity. Interestingly, the antipeptide antibodies obtained exhibited a cross-neutralizing activity for different RV strains in vitro. In addition, the induced antibodies against recombinant proteins also reacted successfully with relevant proteins and with whole virus particle (HRV-74) and other variant strains, as shown by ELISA. They also showed strong crossneutralizing ability against various variants of RVs. Based on the antibody cross-reactivity and neutralization towards different studied serotypes, the selected RV strain HRV-74 seemed to be the type of choice for developing RV broad protective vaccine and multiple RVs antibody based on detection assay. The findings have indicated that the peptides corresponding to the conserved region of the RV capsid proteins are potent immunogenic and suggest that their combination is crucial for extending the cross-protection against variant RVs. Such an alternative approach may raise hope for designing a novel broad-protective vaccine towards non-cultivable, hyper variable pathogen.